Organometallic Complex Strongly Impairs Chikungunya Virus Entry to the Host Cells - Oliveira, Débora Moraes de; Santos, Igor de Andrade; Martins, Daniel Oliveira Silva; Gonçalves, Yasmim Garcia; Cardoso-Sousa, Léia; Sabino-Silva, Robinson; Von Poelhsitz, Gustavo; Franca, Eduardo de Faria; Nicolau-Junior, Nilson; Pacca, Carolina Colombelli; Merits, Andres; Harris, Mark; et al. (Frontiers in Microbiology, 2020)
Chikungunya fever is a disease caused by the Chikungunya virus (CHIKV) that is transmitted by the bite of the female of Aedes sp mosquito. The symptoms include fever, muscle aches, skin rash and severe joint pains. The disease may develop into a chronic condition and joint pain for months or years. Currently, there is no effective antiviral treatment against CHIKV infection. Treatments based on natural compounds have been widely studied, as many drugs were produced by using natural molecules and their derivatives. Alpha Phellandrene (α-Phe) is a naturally occurring organic compound that is a ligand for ruthenium, forming the organometallic complex [Ru2Cl4(p-cymene)2] (RcP). Organometallic complexes have shown promising as candidate molecules to a new generation of compounds that presented relevant biological properties, however, there is a lack of knowledge concerning the anti-CHIKV activity of these complexes. The present work evaluated the effects of the RcP and its precursors, the hydrate ruthenium (III) chloride salt (RuCl3H2O) (Ru) and α-Phe, on CHIKV infection in vitro. To this, BHK-21 cells were infected with CHIKV-nanoluciferase (CHIKV-nanoluc), a viral construct harboring the nanoluciferase reporter gene, at the presence or absence of the compounds for 16 hours. Cytotoxicity and impact on infectivity were analyzed. The results demonstrated that RcP exhibited a strong therapeutic potential judged by the selective index > 40. Antiviral effects of RcP on different stages of the CHIKV replicative cycle were investigated; the results showed that it affected early stages of virus infection reducing virus replication by 77% at non-cytotoxic concentrations. Further assays demonstrated the virucidal activity of the compound that completely blocked virus infectivity. In silico molecular docking calculations suggested different binding interactions between aromatic rings of RcP and the loop of amino acids of the E2 envelope CHIKV glycoprotein mainly through hydrophobic interactions. Additionally, infrared spectroscopy spectral analysis indicated interactions of RcP with CHIKV glycoproteins. These data suggest that RcP may act on CHIKV particles, disrupting virus entry to the host cells. Therefore, RcP may represent a strong candidate for the development of anti-CHIKV drugs.